PENGELOLAAN HOMESTAY SESUAI PROTOCOL COVID-19 DI DESA WARGASARA, KABUPATEN SERANG, PROVINSI BANTEN - Bangga Prameswara (Warta Pariwisata, 2022)
Corona Virus Disease 19 or also known as Covid-19 is currently having a huge impact on the Indonesian tourism industry. Most of the tourism business players in Indonesia were forced to stop their business operations. During the quarter the first of 2020, international tourist arrivals fell by 60-80%. This shows that the current state of tourism it's in bad shape. To anticipate the spread of Covid-19, the Indonesian government has made a standard health protocols that will be applied in the tourism sectors, such as hotels, tourist destinations, restaurants, and homestays existing in Indonesia. Especially in the homestay sector, the results of observations made show that not all homestays apply the covid-19 protocol for their businesses, but there are also districts that already have certificates "new normal" issued by experts from the health department for businesses that have passed the health protocol test, namely Banyuwangi Regency. This is what attracts researchers to conduct a study on how to apply health protocols in the development of homestays in Indonesia, especially those in Serang Regency. The purpose of this research is to know the Homestay Management Standards in Serang Regency and Prepare the Development of Homestay Management Standards According to the COVID-19 Protocol. The data collection techniques used The method used is by observation, interviews, literature studies, and documentation which will later be analyzed with models qualitative descriptive data analysis, namely data reduction, data presentation, and drawing conclusions. The results of this study are known that several homestays in Serang Regency have implemented the COVID-19 protocol although not optimally, such as only preparing hand washing facilities with soap, using masks, cleaning rooms with soap spraying disinfectant, and keeping a distance. There are also homestays that are not so strict in implementation COVID-19 protocols, there are even homestays that do not implement the COVID-19 protocol at all. The preparation of developing homestay management standards according to the COVID-19 protocol is for managers and guests mandatory to use masks in the homestay area, the use of face shields for managers and guests in the homestay area is very recommended to reduce the risk of exposure to COVID-19, Managers are required to use rubber gloves in the area homestay, the manager must provide public hand washing at the location before entering the homestay area, the manager must check body temperature to anyone who enters the homestay area (body temperature is not more than 37.3ºc) and ensure that the party is in a healthy condition (managers, employees, guests, other parties who concerned), the homestay manager is obliged to provide public hand sanitizer in a location that is easily visible and easy to be reached, guests are required to bring their own additional masks and hand sanitizers, the homestay manager must provide AC/fan is in proper condition to ensure good air circulation, homestay manager is mandatory clean guest rooms by spraying disinfectant regularly at least when the room is finished used by guests, homestay managers must install flyers/signs/stickers regarding the COVID-19 protocol in places that are easily visible, all parties must communicate/interact by implementing physical distancing.